Evaluation of vestibular evoked myogenic potential values in elder patients with hip fractures: A prospective controlled study - Topal, Kübra; Uğur, Fatih; Topal, Murat; Atalay, Fatma; Uğur, Emel (SelSistem, 2023)
Background/Aim: Hip fractures among the elderly are a major public health problem that cause high rates of morbidity and mortality. There are many studies regarding prevention and defining the underlying causes of hip fractures. The purpose of this study was to evaluate the cervical vestibular evoked myogenic potential (cVEMP) test responses of elderly patients without vestibular symptoms hospitalized due to fall-related hip fractures in order to evaluate the subclinical vestibular dysfunction rates in patients with hip fractures. Methods: Twenty-two patients aged 67-79 hospitalized due to fall-related hip fractures and 24 control patients presenting to the orthopedic clinic due to knee pain were included in the study. The participants underwent detailed otological examination and cVEMP tests. The two groups’ cVEMP records were then compared. Results: The demographic characteristics of the participants in the patient and control groups including age, gender, and race were similar. There was no statistically significant difference between the groups’ absent VEMP response rates. No significant difference in terms of P1 and N1 latencies was determined between the right and left ears in either group. The hip fracture group (study group) had significantly increased P1 and N1 latencies in cVEMP which is associated with central vestibular dysfunction. (P=0.008 and P=0.007, respectively). Conclusion: The rate of subclinical peripheral vestibular dysfunction, which can be identified by cVEMP evaluation, is increased in elderly patients with hip fractures caused by low energy trauma. Precautions like vestibular rehabilitation can be a preventive measure for hip fractures in the elderly.
Keywords: 3. Good health